Noninvasive Cerebrovascular Diagnosis - AbuRahma, Ali F.; Bergan, John J.; SpringerLink (Online service) (London : Springer London, 2010)
"Noninvasive Cerebrovascular Diagnosis" is the newest definitive text on the current techniques used in assessing vascular disorders. Readers will receive authoritative information and will be guided through the establishment and accreditation of a vascular laboratory and introduced to the physics of diagnostic testing. Chapters, written by selected experts, comprehensively explain the use of ultrasound in diagnosing cerebrovascular, renovascular, visceral ischemia and peripheral arterial disease as well as venous disorders and deep abdominal vascular conditions. Noninvasive Vascular Diagnosis contains over 300 illustrations, many of them in colour. Due to the special sections which give clinical correlations, this book will be invaluable to physicians who treat vascular disorders, surgeons, cardiologists, vascular radiologists and the vascular laboratory staff.
Overview of Cerebrovascular Disease -- Overview of Various Noninvasive Cerebrovascular Techniques -- Duplex Scanning of the Carotid Arteries -- The Role of Color Duplex Scanning in Diagnosing Diseases of the Aortic Arch Branches and Carotid Arteries -- Vertebral Artery Ultrasonography -- Transcranial Doppler Sonography -- Ultrasonic Characterization of Carotid Plaques -- Carotid Plaque Echolucency Measured by Grayscale Median Identifies Patients at Increased Risk of Stroke during Carotid Stenting. The Imaging in Carotid Angioplasty and Risk of Stroke Study -- Duplex Ultrasound in the Diagnosis of Temporal Arteritis -- Duplex Ultrasound Velocity Criteria for Carotid Stenting Patients -- Use of Transcranial Doppler in Monitoring Patients during Carotid Artery Stenting -- Use of an Angle-Independent Doppler System for Intraoperative Carotid Endarterectomy Surveillance -- Clinical Implications of the Vascular Laboratory in the Diagnosis of Cerebrovascular Insufficiency.
Keywords: Medicine; Radiology, Medical; Diagnosis, Ultrasonic; Neurology; Medicine & Public Health; Imaging / Radiology; Ultrasound; Neurology